Association between sleep duration and sarcopenic obesity: The mediating role of hemoglobin level - Xiaojiang Zhao; Jun Chen; Lei Zhang; Hebao Wen; Laiguo Han; Hong Ding (PLoS ONE, 2026)
Background Sarcopenic obesity (SO) is a major global health concern linked to sleep duration. This study examined the association between sleep duration and SO in middle-aged and older Chinese adults, with hemoglobin level as a mediating factor. Methods This research examined data from the 2015 China Health and Retirement Longitudinal Study (CHARLS), focusing on individuals aged 45 years and older. We investigated the link between sleep duration, hemoglobin level, and SO using multivariate logistic regression, adjusting for confounders. A mediation model assessed hemoglobin’s role in the sleep duration-SO relationship. Nonlinear relationships were explored with restricted cubic spline fitting, and likelihood ratio tests evaluated threshold effects. Subgroup analysis examined group heterogeneity. Results After adjusting for covariates, both sleep duration and hemoglobin level were negatively associated with SO. For each unit increase in sleep duration, the association with SO decreased by 9% (OR = 0.91, 95%CI: 0.87–0.95, p < 0.001). For each unit increase in hemoglobin level, the association was reduced by 25% (OR = 0.75, 95%CI: 0.71–0.80, p < 0.001). Hemoglobin had an indirect effect on the relationship between sleep duration and SO, accounting for 11.01% of the total effect variation (−1.20 × 10⁻³, 95%CI: −2.20 × 10⁻³ to 3.30 × 10⁻⁴). Conclusion The study found that both sleep duration and hemoglobin level were negatively associated with SO, and hemoglobin level mediated the relationship between sleep duration and SO.